(untitled) (Al-Academy, 2025)
This research aims to explore the role of sustainable textile art in promoting environmental sustainability through the recycling of consumed materials and their application in contemporary artistic creations. A descriptive-analytical research method was adopted to investigate recycling techniques and the artistic expression possibilities of sustainable textile art. The purposive sample consisted of contemporary artists (5 Artworks) of those who incorporated recycling into their art. In addition to another purposive sample (4 artworks) done by the first author, the researcher used various techniques for reusing materials in artworks through her artistic experiment. The results indicated that sustainable textile art contributes to raising environmental awareness and provides innovative artistic solutions for utilizing waste materials, supporting the concept of eco-friendly art.